Cultivating Financial Savvy: Educational Strategies for Lifelong Financial Wellness in African continent - Amana, Sarah (International Journal of Finance, 2025)
Purpose: Africa faces significant challenges in financial literacy, with only 27% of adults in Sub-Saharan Africa possessing basic financial knowledge. This deficiency has contributed to economic inequalities, poor financial decision-making, and limited access to financial services. Rural populations, women, and marginalized communities remain disproportionately affected. Despite technological advancements, such as mobile banking, the continent continues to grapple with low literacy levels necessary for effective financial inclusion. Addressing these issues requires context-specific educational strategies to empower individuals and foster economic resilience across the African continent. The study aimed to explore and propose educational strategies tailored to Africa's socio-economic and cultural diversity to enhance financial literacy and promote lifelong financial wellness. The study was anchored on the Human Capital Theory, emphasizing the transformative power of education on individual and societal economic outcomes. Methodology: A qualitative research design was adopted, employing content analysis to evaluate secondary data sources, including case studies, reports, and scholarly articles. Findings: The study revealed significant regional disparities in financial literacy across Africa, with rural and marginalized groups being the most affected. Financial education significantly improved economic resilience, decision-making, and intergenerational financial wellness. Global case studies demonstrated the effectiveness of culturally relevant and digitally integrated educational programs. Unique Contribution to Theory, Policy and Practice: It concluded that targeted, collaborative efforts are essential for addressing Africa’s financial literacy gaps. Based on the above, the paper recommended that stakeholders should priorities the development of culturally relevant, scalable financial literacy programs that integrate digital tools and address socio-economic and regional disparities across Africa.